Evaluación de la gestión financiera del gobierno local de la provincia de San Martin en el periodo 2008 - Soria Bardales, Norman (2009)
The topic of this work, refers to the study of evaluation of the financial management of the local government of the province of St Martin in the period 2008. The methodology of investigation (research) for the obtaining of the information was done across technologies (skills) of the interview, survey of questionnaire, direct observation and I gather of the information documentaria; they were polled to 220 persons, of which 140 were hard-working. The tabulations were done manually but with help of the software Excel. The form or reality is studied by the one that comes crossing the municipal finance of San's Martin province, in spite of the fact that we are in the year 2009, it seems to be incredible that still(yet) we have not found a balance between(among) what it(he,she) means to manage for a very short space a municipality(corporated town) that is to the service of the people(village) versus negotiations where the managers of shift believe that overnight they obtained a title deed of the order and therefore the management must suffer a series of mistakes, incompetences and immorality. On the other hand the evaluation presupuestal indicates that I try the municipality (corporated town) of the study can approve an evaluation a priori, but it is necessary to go more thoroughly to determine one new ways of managing this type of institutions, where the users interfere more in the management, and hereby it could control the resources assigned for the province. I conclude that the financial management of the local governments allows to optimize the presentation(service) of the projects mas not of the municipal services in benefit of the citizens, who would have to rationalize processes, integrating(repaying) the different functional areas across the systems of managerial information, establishing channels of direct communication with the neighbors. In case of our object of study, the financial evaluation of the projects executed by San's Martin municipality (corporated town) they give a result of 77 % of advance presupuestal.